2020
DOI: 10.1089/zeb.2020.1917
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pronase, Sodium Thiosulfate, and Methylene Blue Combinations on Development and Survival of Sodium Hypochlorite Surface-Disinfected Zebrafish (Danio rerio) Embryos

Abstract: Embryo surface disinfection is utilized in aquaculture to decrease the risk of pathogen introduction into established colonies. Zebrafish embryos are commonly disinfected with unbuffered sodium hypochlorite at 25-50 ppm for 10 min with or without concurrent treatment with chemicals, including pronase (Pron), sodium thiosulfate, and/or methylene blue; however, the impact of these chemicals on embryo survival and development has not been evaluated. In this study, AB and casper embryos were exposed to disinfectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Finally, we also observed that the CSH concentration (0.0001%) of MB induces early hatching. Previous studies reported conflicting results regarding the effect of MB exposure on hatching 43,44,57 . Because chemical exposure-dependent alterations in hatching time have been reported as endpoint in zebrafish toxicity testing 65 , future studies should investigate possible interactive effects of MB and test chemicals on this endpoint in toxicity screening studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, we also observed that the CSH concentration (0.0001%) of MB induces early hatching. Previous studies reported conflicting results regarding the effect of MB exposure on hatching 43,44,57 . Because chemical exposure-dependent alterations in hatching time have been reported as endpoint in zebrafish toxicity testing 65 , future studies should investigate possible interactive effects of MB and test chemicals on this endpoint in toxicity screening studies.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the long-known metabolic effects of MB, it remains unknown whether currently recommended MB concentrations affect early zebrafish metabolism, and thus may act as a widespread confound in experimental approaches using early zebrafish. Indeed, possible effects of MB on zebrafish (eleuthero)embryos have only very recently begun to be investigated [43][44][45][46][47] . The few studies published to-date focused on overt developmental and behavioural endpoints but yielded conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, MB was shown to photo-inactivate bacteria in 1928 [ 20 ], and its potent antiviral effects were discovered soon after [ 21 ]. MB can also be used as an anti-fungal and anti-parasitic aquarium disinfectant, even with very high dosages (millimolar) [ 22 , 23 ]. MB has also been used in photodynamic therapy among different types of cancers, including lung cancer [ 24 ], breast cancer [ 25 ], and prostate cancer [ 26 ].…”
Section: Structure and Functionsmentioning
confidence: 99%